Estimating the cost-effectiveness of daclatasvir + sofosbuvir versus sofosbuvir + ribavirin for patients with genotype 3 hepatitis C virus - Phil McEwan; Samantha Webster; Thomas Ward; Michael Brenner; Anupama Kalsekar; Yong Yuan (Cost Effectiveness and Resource Allocation, 2017)
Abstract Background As treatments for chronic hepatitis C are moving away from interferon-containing regimens, the most appropriate allocation of resources to higher cost, interferon-free, direct-acting antiviral (DAA) regimens needs to be assessed. Hepatitis C virus (HCV) genotype 3 is associated with faster disease progression and has fewer treatment options, historically, than other HCV genotypes. This analysis aims to estimate the comparative cost-effectiveness of two recently licenced interferon-free regimens for the treatment of HCV genotype 3. Methods Utilising a published Markov model and results of a matching-adjusted indirect comparison of recently published clinical trial data (ALLY-3 and VALENCE, respectively), 12 weeks of treatment with daclatasvir + sofosbuvir (DCV + SOF) was compared to 24 weeks of treatment with sofosbuvir + ribavirin (SOF + RBV). UK-specific model inputs were used to inform a cost-utility analysis of these regimens. Results In the base case analysis, DCV + SOF was found to be dominant over SOF + RBV in treatment-naïve patients, patients that had previously been treated, and patients that are intolerant to, or ineligible for, interferon-containing regimens. Given the low rates of treatment currently observed in the UK, DCV + SOF was also compared to no treatment in the interferon-ineligible/intolerant patients, and may be considered cost-effective with an incremental cost-effectiveness ratio of £8817. Conclusions When compared to 24 weeks of SOF + RBV, 12 weeks of treatment with DCV + SOF results in improved quality of life and reduced total costs, and therefore is likely to represent significant clinical and economic value as a treatment option for genotype 3 HCV infection.